Clinical parameters in patients with halitosis: a cross-sectional study - Ahoud Jazzar; Hebah AlDehlawi; Arwa Farag; Sana Alhamed; Sara Akeel; Yasmin Mair; Kenana Flemban; Hidaya Alqassab; Khalid Aljohani (Frontiers Media S.A., 2024)
BackgroundHalitosis, a socially and psychologically impactful condition often resulting from oral or systemic issues, is exacerbated by factors like aging, poor oral hygiene, and dietary choices. This study aimed to investigate the association between halitosis and stress by measuring salivary cortisol levels and the Cohen's Perceived Stress Scale (CPSS).MethodsA cross-sectional study of 40 participants was conducted using questionnaires and clinical measurements to assess halitosis and stress levels. Saliva samples were collected and analyzed for cortisol using ELISA. Participants' stress was assessed with the Cohen's Perceived Stress Scale Questionnaire (CPSS-10) questionnaire, and halitosis was measured with a Halimeter and self-assessment questionnaire. Clinical measurements included Plaque Index (PI) and the Decayed, Missing, and Filled Teeth (DMFT) score.ResultsForty subjects were split into a halitosis group (mean age 30.75 ± 10.15) and group with no halitosis (mean age 26 ± 5.3). Objective measures confirmed higher halitosis scores (3.70 ± 0.73) in the halitosis group vs. the second group (2.60 ± 1.67). Compared with the group with no halitosis, the halitosis group exhibited significantly (p < 0.05) more plaque (27.92% ± 17.16% vs. 47.50 ± 33.57%; p < 0.05) and higher DMFT scores (10.10 ± 2.51 vs. 26 ± 5.30), respectively. Salivary cortisol levels were similar across groups (1.721 ng/ml halitosis, 1.781 ng/ml without halitosis). Correlations showed a moderate positive relationship between DMFT and halimeter scores (r = 0.377, p = 0.018) and a moderate negative correlation between stress and plaque index (r = −0.403, p = 0.011), with no correlation between halimeter score and cortisol or CPSS score.ConclusionsOur findings showed that while halitosis severity correlated with higher DMFT scores and plaque accumulation, there was no significant association with salivary cortisol levels, suggesting that stress, as measured by salivary cortisol, may not be a direct contributor to halitosis. Furthermore, the data suggest that poor oral hygiene is a more significant factor in the development of halitosis than stress levels, as assessed by the CPSS-10.